Evaluation of the Regional Spatial Plan for Settlements in Siak District Based on Flood Prone Area - ANWAR, AZHARIL NAUFAL; Umar, Iswandi (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to determine the RTRW inconsistency index by analyzing the implementation of the Siak District Settlement RTRW, which is known from the comparison between land use and the Siak District RTRW. The land use map is generated from the SAS Planet high-resolution mind, and the settlement spatial plan map is generated from the 2020–2040 RTRW in Siak District. In addition, to find out the Siak District Settlement Spatial Plan based on disaster-prone areas, a flood disaster-prone analysis was carried out using the